Antibiotic Resistance in Filters from Car Air Conditioning Systems - Agnieszka Jurkowska; Agnieszka Tabernacka; Ewa Karwowska (Applied Sciences, 2025)
In the present study, a quantitative analysis of culturable microflora of car cabin filters was accomplished, with a special focus on bacteria resistant to some antibiotics. The occurrence of antibiotic-resistant bacteria was considered in the filters with activated carbon and filters with antibacterial properties. The minimum inhibitory concentration was evaluated for selected bacterial strains isolated from the filters. It was found that cabin filters after long-time operation are not only heavily contaminated with bacteria and fungi but also constitute a habitat for numerous antibiotic-resistant bacteria. The numbers of culturable bacteria resistant to penicillin, nitrofurantoin, rifampicin, doxycycline, or gentamicin reached 102–103 CFU/g of filter material. No relationship was observed between car brand or filter type and the abundance of antibiotics-resistant bacteria. The lower bacterial content of antibacterial filters was not accompanied by a proportionally lower content of resistant microorganisms which may indicate that the present techniques are not sufficient to limit their growth effectively. Pseudomonas sp. isolates from the filter material were not sensitive even in relation to high concentrations of some antibiotics, which confirms their significant resistance potential and may be important in the context of the spread of drug resistance in the vehicles indoors.